Strategi caching aplikasi berbasis in-memory menggunakan Redis server untuk mempercepat akses data relasional - Mulki Indana Zulfa; Ari Fadli; Arief Wisnu Wardhana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2020)
Utilization of an in-memory database as a cache can overcome relational database latency problems in a web application, especially when using a lot of join queries. This study aims to model the academic relational data into Redis compatible data and analyze the performance of join queries usage to accelerate access to relational data managed by RDBMS. This study used academic data to calculate student GPA that is modeled in the RDBMS and Redis in-memory database (IMDB). The use of Redis as an in-memory database can significantly increase Mysql database system performance up to 3.3 times faster to display student data using join query and to shorten the time needed to display GPA data to 52 microseconds from 61 milliseconds.